Studies on Some Anaerobic Rumen Bacteria With Special Reference to Their Endoglucanase Gene - Wong, Clemente Michael Vui Ling (1996)
Four strains of Fibrobacter succinogenes (DI, D3, D5 and D6) and 3 strains of Ruminococcus flavefaciens eMD-I, MD-8 and MD-9) were found to be highly fibrolytic, degrading and solubilising Whatman No.1 filter paper strips in Scott and Dehority medium within 16-48 h. Among the 7 bacterial strains, F. succinogenes D3 and R. flavefaciens MD-1 were two of the most active, being able to solubilise the filter paper strip within 16-24 h, and were used for endoglucanase assay. R. flavefaciens MD-1 produced significantly higher endoglucanases activity than F. succinogenes D3 at all incubation periods.